2015
DOI: 10.1039/c5ra09483f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterisation and application of imidazolium based ionic liquid modified montmorillonite sorbents for the removal of amaranth dye

Abstract: The removal of amaranth dye using montmorillonite modified with an ionic liquid (IL) wasinvestigated. An ionic liquid (1-methyl, 3-decahexyl imidazolium) was synthesised, and characterised by nuclear magnetic resonance ( 1 H and 13 C NMR), fourier transform infrared (FT-IR) spectroscopy, high resolution mass spectroscopy (HR-MS) as well as thermal gravimetric analysis and differential thermal (TGA/DCS) analysis. The ionic liquid was thereafter used to modify sodium montmorillonite (Na+-Mt) to form a hydrophobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 71 publications
2
18
0
Order By: Relevance
“…This showed that modifying KP with IL has significantly increased it sorption capacity. Similar outcomes have been reported by other researchers …”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…This showed that modifying KP with IL has significantly increased it sorption capacity. Similar outcomes have been reported by other researchers …”
Section: Resultssupporting
confidence: 92%
“…) show the decomposition of KP. KP is rich in H and O contents, and the peaks in the region 3000–3690 cm −1 were assigned to –OH and ‐NH groups; intense peaks at 2915 and 2850 cm −1 on KP‐IL were assigned to symmetric and asymmetric stretching vibrations of the methylene groups in the ionic liquid showing the modification of the biomass with ionic liquid molecules . These peaks were not as pronounced in the unmodified plant material.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Among adsorbents, montmorillonite proved to be a suitable material for water remediation. The hydrophilic properties of the montmorillonite surface are changed to hydrophobic ones through modification by surfactants to form organo‐montmorillonite , , for the purpose of adsorbing organic pollutants. When introduced at low concentration into a system, surfactants are able to adsorb onto the surfaces or interfaces of the system, thereby altering to a certain degree the surface or interfacial free energies of such surfaces or interfaces .…”
Section: Introductionmentioning
confidence: 99%